2018
DOI: 10.11607/ofph.1912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Physical Therapy Protocol in Patients with Chronic Migraine and Temporomandibular Disorders: A Randomized, Single-Blinded, Clinical Trial

Abstract: Aims: To investigate the effects of adding orofacial treatment to cervical physical therapy in patients with chronic migraine and temporomandibular disorders (TMD). Methods: A total of 45 participants with chronic migraine and TMD aged 18 to 65 years were randomized into two groups: a cervical group (CG) and a cervical and orofacial group (COG). Both groups continued their medication regimens for migraine treatment and received physical therapy. The CG received physical therapy only in the cervical region, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 65 publications
(89 reference statements)
3
48
0
14
Order By: Relevance
“…The average subject age was 41.5 years. The studied pathologies included mouth opening pain [ 18 , 19 , 21 , 22 ], mouth opening limitation [ 19 , 20 , 22 ], myofascial symptoms [ 14 , 18 , 19 ], non-reducing disc displacement [ 19 , 20 ] and chronic migraine [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average subject age was 41.5 years. The studied pathologies included mouth opening pain [ 18 , 19 , 21 , 22 ], mouth opening limitation [ 19 , 20 , 22 ], myofascial symptoms [ 14 , 18 , 19 ], non-reducing disc displacement [ 19 , 20 ] and chronic migraine [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of TMD is usually addressed with several therapies, including splints, psychotherapy [ 10 , 11 ], acupuncture [ 12 ], and various physiotherapy techniques such as transcutaneous electrical nerve stimulation (TENS), lasers, massage therapy [ 13 ], joint mobilization and therapeutic exercise (TE) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study showed that cervical and orofacial treatment was more effective than cervical treatment alone to increase PPTs in the trigeminal area of patients with TMD and migraine. Thus, treating solely the neck, as we did on the present study, is probably not enough to enhance sensibility of the masticatory muscles, but associating techniques on the stomatognathic system and on the neck would be more effective.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with these results, previous studies have shown that isolated upper cervical manual techniques, including SNAG mobilisation and suboccipital muscle inhibition, caused significant reduction in headache severity compared to a placebo group when applied to subjects with cervicogenic and tension‐type headaches. The application of manual therapy techniques to the cervical spine in combination with exercise has been shown to be effective in reducing pain in patients with tension‐type headaches, with cervicogenic headache, with migraine, but, to the best of our knowledge, remains unknown for secondary headache attributed to TMD.…”
Section: Discussionmentioning
confidence: 99%